Сurrent issues of monitoring theory and practice in pedagogical higher educational institutions as a factor of the quality of education - Repko, Inna; Stepanets, Ivan; Odarchenko, Veronika (My University, 2022)
The article attempts to generalize the results of scientific investigations of domestic scientists and the experience of the staff of the MUNICIPAL ESTABLISHMENT «KHARKIV HUMANITARIAN-PEDAGOGICAL ACADEMY» of KHARKIV REGIONAL COUNCIL regarding the monitoring in pedagogical institutions of higher education as a factor of improving the quality of the educational process. The issue of the theory and practice of monitoring research in pedagogical higher educational institutions was considered, in particular: common theoretical regulations characterizing the unity of the authors‘ approaches to the consideration of the monitoring phenomenon were established, its essential characteristics were highlighted; the place, role and advantages of monitoring in the higher education system and its direct impact on ensuring the quality of the educational process are defined; the objects of monitoring at the university, faculty and departmental levels are named; aspects of monitoring studies are characterized; the criterion base characterizing the essential aspects of pedagogical education and the corresponding parameters for individual criteria are determined. Based on the results of generalization of experience, an annual cyclogram of educational monitoring in higher educational institutions was formed. The analysis of the array of scientific research results made it possible to determine the prospects for further research on the problem of monitoring in pedagogical higher educational institutions.
Repko I. Сurrent issues of monitoring theory and practice in pedagogical higher educational institutions as a factor of the quality of education / I. Repko, I. Stepanets, V. Odarchenko // Еnrichment of the pedagogical cluster of educational services: International collective monograph / edited by G. F. Ponomarova, A. A. Kharkivska, L. O. Petrychenko and other; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council. – Kharkiv- Praha : Oktan print s.r.o., 2022. – Р. 55–81.
Keywords: заклад вищої педагогічної освіти, моніторинг, об‘єкти моніторингу, якість педагогічної освіти, рівні та аспекти моніторингу, напрями та критеріальна база оцінювання якості педагогічної освіти; pedagogical higher educational institution, monitoring, objects of monitoring, the quality of pedagogical education, levels and aspects of monitoring, directions and criterion base for evaluating the quality of pedagogical education